'GRASS BANKS BETWEEN THE STORAGE TANKS': 20TH-CENTURY INDUSTRY ON THE HOO PENINSULA, KENT. (May 2014) - Carpenter, Edward
Abstract : The Hoo Peninsula is situated on the north Kent Coast, bounded by the rivers Thames and Medway. A third of the peninsula is low-lying and includes expansive marshland protected by substantial sea walls. Perceptions of Hoo are often associated with these remote, open areas populated with grazing animals and wild birds. But mention of the Hoo Peninsula can also evoke an entirely different set of images predominantly associated with 20th-century industry. These industries, which were established on Hoo from the mid-19th century, were based on new technologies and new materials such as cement, chemical explosives, oil refining, communications and power generation. A recent English Heritage multi-disciplinary project has revealed the impact and legacy of these industries on Hoo.